Intravenous fluid delivery time improvement: application of cross-docking system. - Khorasani, Sasan T.; Keshtzari, Maryam; Islam, Md Saiful; Feizi, Ramyar (International Journal of Health Care Quality Assurance (09526862), 2018)
Purpose: The cost of pharmaceutical supply chain due to drug waste is one of the current major issues in health care. Drug waste associated with intravenous (IV) fluid form of medication is one of the crucial issues for many pharmacies. The purpose of this paper is to apply a cross-docking model to minimize the IV delivery lead time to reduce drug waste by scheduling staff in a local hospital's inpatient pharmacy.Design/methodology/approach: A mixed integer linear programming model is applied to the IV delivery system of a hospital. The parameters are selected based on the observations made in the inpatient pharmacy.Findings: The result implies that cross-docking approach can be effectively applied to IV delivery system. In fact, the cross-docking optimization model employed in this case study reduces the IV delivery completion time of the inpatient pharmacy by 41 percent.Research Limitations/implications: The scope of this research is limited to the activities performed after IV preparation.Practical Implications: The application of cross-docking system in staff scheduling will be beneficial for health care organizations that aim to minimize medication waste.Originality/value: The prime value of this study lies in the introduction of a cross-docking concept in an internal hospital ordering process. Cross-docking models are widely used in general supply chain systems; however, their application for specific activities inside hospitals is the novelty of this study, which can fill the research gap in terms of drug waste management within the inpatient pharmacy.